ChemInform Abstract: Skeletally Diverse Synthesis of Indole‐Fused Diazocine and Diazepine Frameworks by One‐Pot, Two‐Component Cascade Reaction. Issue 21 (6th May 2016) - Thikekar, Tushar Ulhas; Selvaraju, Manikandan; Sun, Chung‐Ming
Abstract: The substrate base‐diversification approach offers a straightforward access to a library of compounds with immense interest in drug discovery.